The influence of facilities on fish quality in ports of east waters, North Sumatera (case study in belawan fishing port, North Sumatera) - Ratih Purnama Sari; Yaser Krisnafi; Mathius Tiku; Roma Yuli F Hutapea; Suci Asrina Ikhsan; Ratu Sari Mardiah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
One of the problems faced in the development of the marine and fisheries sector nationally is the low quality of the fish capture due to the limited capacity and quantity of available port infrastructure resulting in the decrease in competitiveness. The data in this study were related to fish capture from fishing boats to wholesalers. The data obtained was observation of the location of the vessel, the fish auction place, and the marketer. The types of fish taken were Kurisi (Nemipterus pneumatophores), Biji Nangka (Upeneus mullocensin), Kapas-Kapas (Gerres erythronium), Bawal Putih (Pampus argenteus), Kembung (Rastrelliger spp). Fish examining was done by looking at the organoleptic and pH values. The pH value was obtained by testing the pH meter, while the organoleptic value was obtained by observing the physical condition using a score sheet. To determine the magnitude of the influence of facilities on fish quality, and the correlation between organoleptic values and pH, an analysis using simple linear regression was conducted. The average organoleptic value of fish while on the boat, when distributed, and when in the marketplace were 8,248; 7,024; and 6.6 respectively. Meanwhile, the average pH value was 7.05; 5.51; and 5.15. The quality of fish caught at Class A Fishing Port of Belawan is still of good quality. The pH test showed decline in pH value ever since the fish was brought to the port until they were marketed. The influence of facilities on the fish organoleptic and pH value are 98.3% and 96%. Thus, facilities significantly affect fish quality at Belawan Fishing Port. Between pH and organoleptic values showed a positive correlation, hence when the pH value decreased, the organoleptic value also dropped.Keywords:Belawan Fishing PortEast WatersFacilities InfluenceFish Quality